Pengaruh Pupuk Organik Terhadap Pertumbuhan Dan Hasil Kacang Tanah (Arachis Hypogaea) - Machsi Firall Tishuathi Mendrofa; Areani Zebua; Forniwati Harefa; Romanus Restu Gulo; Yupika Ananda Mendrofa; Yoel Melsaro Larosa; Putra Hidayat Telaumbanua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to evaluate the effects of various types of organic fertilizers on the growth and yield of peanuts (Arachis hypogaea). Several studies have shown that the application of organic fertilizers—such as chicken manure, rice straw compost, and liquid organic fertilizer (POC)—significantly increases the vegetative and generative growth of plants. This occurs because organic fertilizers improve soil structure, increase water retention capacity, and provide essential nutrients such as nitrogen (N), phosphorus (P), and potassium (K). The combination of organic and inorganic fertilizers is known to produce yields up to 59.43% higher than without fertilizer. In addition, the use of organic fertilizers supports environmental sustainability and increases the activity of soil microorganisms that play a role in the decomposition and mineralization of nutrients. Therefore, the use of organic fertilizers is an important strategy in realizing a sustainable and productive agricultural system.